Endodontic management of mandibular premolars with three root canals: Case series - Yousef Hamad Al-Dahman; Saeed Ali Al-Qahtani; Abeer Abdulkareem Al-Mahdi; Abdullah Yousef Al-Hawwas (Wolters Kluwer Medknow Publications, 2018)
The proper knowledge of both the external and internal anatomy of teeth is mandatory for adequate root canal treatment. Permanent mandibular premolars are usually single rooted with single root canal. Variations of having more than one canal/root also exist. This paper describes a case series of root canal therapy of permanent mandibular premolars with three root canals. The clinicians must be aware of such anatomical variations and be able to use variety of tools for adequate diagnosis and management.